BRAIN STRUCTURES INVOLVED IN TIME PERCEPTION - Chandra bhushan Prasad (International Journal of Multidisciplinary Research and Studies, 2021)
Over the course of the last several years, there has been considerable development in the field of instrumental examination and evaluation of consciousness and its disorders (DOCs, also known as coma, vegetative state/unresponsive wakefulness syndrome, or VS/UWS, and minimally conscious state, or MCS). This progress has resulted in, among other things, the transition from a singular way of looking at severe brain damage to a more graded nosology. This graded nosology is based on a quantitative assessment of consciousness and on functional neuroimaging technologies. Other benefits of this progression include: The so-called "neuro-technologies," in particular the application of technology to the evaluation and exploration of consciousness, have resulted to discoveries that are both stunning and unanticipated, and these results have profound theoretical and practical ramifications.